Two haplotypes of the P2X₇ receptor containing the Ala-348 to Thr polymorphism exhibit a gain-of-function effect and enhanced interleukin-1β secretion - Stokes, Leanne; Fuller, Stephen J; Sluyter, Ronald; Skarratt, Kristen K; Gu, Ben J; Wiley, James S (The FASEB journal, 2010)
The P2X₇ receptor is an ATP-gated cation channel expressed in immune cells and plays a role in proinflammatory cytokine release from monocytes and macrophages. This study investigated the coinheritance of 12 functionally relevant single nucleotide polymorphisms (SNPs) in the human P2X₇ gene (P2RX7), and the functional effect of each singly and in combination was assessed by measurements of ATP-induced currents and ethidium⁺ uptake. Genotyping of 3430 Caucasian subjects identified 4 common haplotypes in addition to the common (wild-type) P2X₇-1. Two haplotypes (denoted P2X₇-2 and P2X₇-4) contained various combinations of gain-of-function SNPs. P2X₇-4 was identified uniquely by the Gln-460 to Arg polymorphism (rs2230912). When expressed in HEK-293 cells, recombinant P2X₇-2, and P2X₇-4 haplotypes displayed a 3-fold and 5-fold increase, respectively, in receptor function compared to the wild-type P2X₇-1. Both P2X₇ haplotypes contained the Ala-348>Thr polymorphism (rs1718119), and this mutation was critical for the gain-of-function effect. Peripheral blood monocytes and erythrocytes from subjects homozygous for gain-of-function P2X₇ haplotypes exhibited increased ATP-induced ethidium⁺ uptake and ⁸⁶Rb⁺ efflux, respectively, and this correlated with increased IL-1β secretion from LPS-primed monocytes. Inheritance of these P2X₇ haplotypes predisposing to increased proinflammatory cytokine secretion may be important in genetic association studies of inflammatory, infectious, and psychiatric disorders.--Stokes, L., Fuller, S. J., Sluyter, R., Skarratt, K. K., Gu, B. J., Wiley, J. S. Two haplotypes of the P2X₇ receptor containing the Ala-348 to Thr polymorphism exhibit a gain-of-function effect and enhanced interleukin-1β secretion.